KEADILAN PERSAINGAN USAHA DALAM MENJAMIN KEDAULATAN EKONOMI DESA ADAT DI BALI - Wiryanthi, Ni Putu Ega Maha; Puspadewi, Anak Agung Ayu Intan (VYAVAHARA DUTA, 2025)
Customary villages in Bali now stand at a crossroads between local wisdom and the forces of modern markets. As retail chains like Indomaret, Alfamart, and 24-hour “networked commercial warung” expand deep into traditional communities, local shops begin to lose their foothold. Backed by centralized distribution systems, aggressive promotions, and around-the-clock operations, large-scale businesses dominate the market while leaving little room for traditional village-owned stores. As a result, krama desa (village members) not only suffer economic loss but also the erosion of their social role as community hubs. This study employs a normative legal approach to examine the relationship between national competition law and customary legal systems in protecting local economies. The findings reveal that the lack of synergy between state law and customary law exacerbates the structural inequalities faced by small-scale entrepreneurs. In this context, the law must evolve from a merely formal set of rules into a contextual and inclusive instrument of protection. Strengthening the authority of desa adat through the formal recognition of local regulations such as awig-awig and perarem is a crucial step in restoring balance between economic modernization and communal sustainability. This abstract proposes that economic justice is not solely about market efficiency, but also about the law’s moral obligation to protect the vulnerable.